Validation of Automated Perfusion‐Weighted Phase‐Resolved Functional Lung (PREFUL)‐MRI in Patients With Pulmonary Diseases. Issue 1 (24th December 2019) - Behrendt, Lea; Voskrebenzev, Andreas; Klimeš, Filip; Gutberlet, Marcel; Winther, Hinrich B.; Kaireit, Till F.; Alsady, Tawfik Moher; Pöhler, Gesa H.; Derlin, Thorsten; Wacker, Frank; Vogel‐Claussen, Jens
Abstract : Background: Perfusion‐weighted (Qw) noncontrast‐enhanced proton lung MRI is a promising technique for assessment of pulmonary perfusion, but still requires validation. Purpose: To improve perfusion‐weighted phase‐resolved functional lung (PREFUL)‐MRI, to validate PREFUL with perfusion single photon emission computed tomography (SPECT) as a gold standard, and to compare PREFUL with dynamic contrast‐enhanced (DCE)‐MRI as a reference. Study Type: Retrospective. Population: Twenty patients with chronic obstructive pulmonary disease (COPD), 14 patients with cystic fibrosis (CF), and 21 patients with chronic thromboembolic pulmonary hypertension (CTEPH) were included. Field Strength/Sequence: For PREFUL‐MRI, a spoiled gradient echo sequence and for DCE‐MRI a 3D time‐resolved angiography with stochastic trajectories sequence were used at 1.5T. Assessment: PREFUL‐MRI coronal slices were acquired in free‐breathing. DCE‐MRI was performed in breath‐hold with injection of 0.03 mmol/kg bodyweight of gadoteric acid at a rate of 4 cc/s. Perfusion SPECT images were obtained for six CTEPH patients. Images were coregistered. An algorithm to define the appropriate PREFUL perfusion phase was developed using perfusion SPECT data. Perfusion defect percentages (QDP) and Qw‐values were calculated for all methods. For PREFUL quantitative perfusion values (PREFULQ ) and for DCE pulmonary blood flow (PBF) was calculated. Statistical Tests: Obtained parameters were assessed using Pearson correlation and Bland–Altman analysis. Results: Qw‐SPECT correlated with Qw‐DCE ( r = 0.50, P < 0.01) and Qw‐PREFUL ( r = 0.47, P < 0.01). Spatial overlap of QDP maps showed an agreement ≥67.7% comparing SPECT and DCE, ≥64.1% for SPECT and PREFUL, and ≥60.2% comparing DCE and PREFUL. Significant correlations of Qw‐PREFUL and Qw‐DCE were found (COPD: r = 0.79, P < 0.01; CF: r = 0.77, P < 0.01; CTEPH: r = 0.73, P < 0.01). PREFULQ /PBF correlations were similar/lower (CF, CTEPH: P > 0.12; COPD: P < 0.01) compared to Qw‐PREFUL/DCE correlations. PREFULQ ‐values were higher/similar compared to PBF‐values (COPD, CF: P < 0.01; CTEPH: P = 0.026). Data Conclusion: The automated PREFUL algorithm may allow for noncontrast‐enhanced pulmonary perfusion assessment in COPD, CF, and CTEPH patients comparable to DCE‐MRI. Level of Evidence 3 Technical Efficacy Stage 2 J. Magn. Reson. Imaging 2020;52:103–114.